Arete and Gender-Differentiation in Socrates/Plato and Aristotle - Robinson, Thomas (1999)
The article grapples with the question whether Plato believed that, in the matter of arete, the female psyche had a built-in inclination to immorality in a way that the male psyche did not, and was therefore assuch signiticantly different from the male psyche. It is argued that the evidence of the Timaeus ( and, to some lesser degree, of the Laws) suggests very strongly that he did, though fortunately the political consequence she drew from this (in the Laws) tum out to be positive rather than negative. Aristotle, by contrast,it is argued, while still holding to the lamentable theory of the inferiority of woman, talks of ditl'eringquanta of (one and the same) arete in male and female souls, rather than a difference in their very arete.